Human Cerebral Perfusion, Oxygen Consumption, and Lactate Production in Response to Hypoxic Exposure. (27th August 2021) - Vestergaard, Mark B; Ghanizada, Hashmat; Lindberg, Ulrich; Arngrim, Nanna; Paulson, Olaf B; Gjedde, Albert; Ashina, Messoud; Larsson, Henrik B W
Abstract: Exposure to moderate hypoxia in humans leads to cerebral lactate production, which occurs even when the cerebral metabolic rate of oxygen (CMRO2 ) is unaffected. We searched for the mechanism of this lactate production by testing the hypothesis of upregulation of cerebral glycolysis mediated by hypoxic sensing. Describing the pathways counteracting brain hypoxia could help us understand brain diseases associated with hypoxia. A total of 65 subjects participated in this study: 30 subjects were exposed to poikilocapnic hypoxia, 14 were exposed to isocapnic hypoxia, and 21 were exposed to carbon monoxide (CO). Using this setup, we examined whether lactate production reacts to an overall reduction in arterial oxygen concentration or solely to reduced arterial oxygen partial pressure. We measured cerebral blood flow (CBF), CMRO2, and lactate concentrations by magnetic resonance imaging and spectroscopy. CBF increased ( P  < 10 −4 ), whereas the CMRO2 remained unaffected ( P  > 0.076) in all groups, as expected. Lactate increased in groups inhaling hypoxic air (poikilocapnic hypoxia: $0.0136\ \frac{\mathrm{mmol}/\mathrm{L}}{\Delta{\mathrm{S}}_{\mathrm{a}}{\mathrm{O}}_2}$, P  < 10 −6 ; isocapnic hypoxia: $0.0142\ \frac{\mathrm{mmol}/\mathrm{L}}{\Delta{\mathrm{S}}_{\mathrm{a}}{\mathrm{O}}_2}$, P  = 0.003) but was unaffected by CO ( P  = 0.36). Lactate production was not associated with reduced CMRO2 . These results point toward a mechanism of lactate production by upregulation of glycolysis mediated by sensing a reduced arterial oxygen pressure. The released lactate may act as a signaling molecule engaged in vasodilation.